Accumulated training load between football players exposed to different playing times: A systematic review - Rago, V.; Figueiredo, P.; Miranda-Gonzalez, C.-E.; Tessitore, A.; Saavedra-García, M. Á.; Nakamura, F. Y.; Sansone, P. (International Journal of Sports Science & Coaching, 2025)
Different long-term exposure to match-play might have implications for maintaining the collective fitness levels within a football team. However, there is a lack of clarity regarding the accumulation of training and match load in football between players regularly exposed to match-play (e.g., starters) and less exposed (e.g., nonstarters, substitutes, non-selected). This study systematically reviewed the subsequent training/match load according to the different playing times of football players. Following the PRISMA guidelines on three electronic databases (PubMed, Scopus, and Web of Science), observational studies performing a formal comparison in training and/or match load between players exposed to different playing times were screened (Prospero registration: CRD42023473037). Twenty-two studies including 484 adult males, 79 adult females and 95 youth males, reported from a minimum of 18 training sessions to a full season. The average methodological quality of the studies was moderate (74.9%). Players were mostly classified by the exposure time to the latest match among other criteria. Still, different cut-off values were adopted within the same criteria. Football players accumulated greater overall (match + training) volume and high-intensity running activities and physiological responses when exposed to greater playing time. However, a similar practice training volume, high-intensity activities, and physiological responses observed between players potentially suggests the reliance on top-up running conditioning strategies for substituted/unselected players adopted to compensate for the lower match load, albeit insufficient to compensate for the match load.